Infrastructural Realization of the Indonesia-Malaysia Cross Border Tourism Concept in Sambas Regency, West Kalimantan - Setya Aristu Pranoto; I Gede Mudana; I Ketut Budarma (Catuspata Press, 2021)
Purpose: This research was conducted in the border area in Sajingan Besar District, Sambas Regency, West Kalimantan, Indonesia, by focusing on the realization of the infrastructure aspect as the driving force of the development of the Indonesia-Malaysia cross border tourism destination. Research methods: The data of the research comes from observations, unstructured interviews, and literature studies. The research method used is qualitative descriptive methods. Findings: The research shows that the Aruk border area has completed both stages: (i) Priority Core Zone (office and service zone, trade and service zone) san (ii) Support Zone (infrastructure such as rest areas, money changers, tourism markets, places of worship, Indonesian guesthouse). Implication: The project needs fulfilment of strong basics such as infrastructure and accommodation, as well as being integrated with each other in building and advancing border areas to become world-class destinations, namely cross border tourism.